Evaluation of maize genotypes against post flowering stalk rot under terai region of Nepal - Subedi, Subash; Neupane, Saraswati; Koirala, Keshab Babu; Oli, Lokendra (Journal of Agriculture and Natural Resources, 2021)
The inadequate source of resistance materials in maize against major biotic stresses is one of the main reasons for considerable loss of grain yield in Nepal. Post flowering stalk rot disease caused by Fusarium moniliforme is a serious disease that exposes high incidence at grain filling stage of maize in terai region of Nepal during summer season. This study was done to evaluate level of resistance, or tolerance in selected genotypes against the post flowering stalk rot disease of maize. Accordingly, thirty maize genotypes were tested for maize stalk rot resistance during summer season of 2016 and 2017 at National Maize Research Program, Rampur (NMRP), Chitwan. The experiment was done under natural epiphytotic condition at hot spot of the disease by using Randomized Complete Block design with 2 replications for each treatment. The package of practices was followed as per national recommendation. The summer season of 2016 and 2017 were affable for post flowering stalk rot of maize at NMRP, Rampur. Out of 30 genotypes, most of the tested entries showed susceptible reaction during both the years; however, RML-95/RML-96, Across-9942/Across-9944, ZM-401, Rampur 34, RamS03F08 and TLBRS07F16 showed resistant reaction against the disease and might be useful for the development of post flowering stalk rot resistant maize varieties for terai region of Nepal.